2019
DOI: 10.1113/jp277267
|View full text |Cite
|
Sign up to set email alerts
|

Region‐specific differences and areal interactions underlying transitions in epileptiform activity

Abstract: Key points Local neocortical and hippocampal territories show different and sterotypical patterns of acutely evolving, epileptiform activity. Neocortical and entorhinal networks show tonic–clonic‐like events, but the main hippocampal territories do not, unless it is relayed from the other areas. Transitions in the pattern of locally recorded epileptiform activity can be indicative of a shift in the source of pathological activity, and may spread through both synaptic and non‐synaptic means. Hippocampal epilep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 56 publications
(121 reference statements)
2
25
0
Order By: Relevance
“…The proportion of brain circuits effected by activity-dependent Claccumulation will vary considerably between patients depending on the seizure type as well as the extent to which different brain areas are recruited into the seizure process. Interactions between areas may also be critical in providing pacemaker drives (Codadu et al, 2018), thereby maintaining a high rate of discharge, but breaking this loop by slightly reducing the intrinsic rate at a particular site may be all that is required. In regions where intracellular Cland EGABA are still low, benzodiazepines will enhance inhibitory restraint.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of brain circuits effected by activity-dependent Claccumulation will vary considerably between patients depending on the seizure type as well as the extent to which different brain areas are recruited into the seizure process. Interactions between areas may also be critical in providing pacemaker drives (Codadu et al, 2018), thereby maintaining a high rate of discharge, but breaking this loop by slightly reducing the intrinsic rate at a particular site may be all that is required. In regions where intracellular Cland EGABA are still low, benzodiazepines will enhance inhibitory restraint.…”
Section: Discussionmentioning
confidence: 99%
“…By recording GABA currents at different holding voltages gGABA could be measured before and after 30 mins exposure to 0 Mg 2+ in the same neuron. GABAB receptor blockade to isolate GABAARs was not utilised as this could interfere with the seizure-like activity evoked by 0 Mg 2+ (Swartzwelder et al, 1987;Codadu et al, 2018). Following termination of SE-like activity using reintroduction of Mg 2+ , gGABA was remeasured.…”
Section: Persistent Epileptiform Activity Is Associated With a Reductmentioning
confidence: 99%
“…Brain slices were prepared in the same way (often from the same animals), from young, adult mice. We showed previously that the two models affect hippocampal and neocortical areas differently 32 (note that the entorhinal cortex appears to align with neocortical activity, rather than the hippocampal circuitry, in this regard), with the hippocampal territories being activated early in 4AP, but very late in 0 Mg 2+ . Here we focused on neocortical activity patterns, and showed that 4AP has an especially strong effect on PV-expressing interneurons (although it also alters, to a lesser extent, activity in both SST-expressing interneurons and pyramidal cells), triggering spontaneous bursting in these cells (similar results have also been reported by Williams and Hablitz 33 ).…”
Section: Discussionmentioning
confidence: 84%
“…Raised extracellular K 1 will also facilitate chloride loading, which is coupled via the cation-chloride cotransporter KCC2. In either case, whether GABAergic output is inhibitory or excitatory, the enhanced coupling of interneurons through their gap junctions is likely to be an important determinant of the complex pattern of propagating local field potentials during a seizure (Viventi et al, 2011;Smith et al, 2016;Codadu et al, 2019b). It is also highly pertinent that gap junction expression is commonly increased in epileptic brains (Manjarrez-Marmolejo and Franco-Pérez, 2016).…”
Section: Discussionmentioning
confidence: 99%